Fouras - Automated Android Accessibility Assessment - Häggander, Hannes (My University, 2025)
This thesis investigates systematic methods and tools applicable to improve the accessibility feature compliance testing of Android applications. Focusing on how software engineers can better implement design their applications to simplify testing and verify compliance with European accessibility standards, such as EN 301 549 [1] and WCAG 2.1 [2]. We aspired to assist developers and organizations in improving their Android application accessibility support and promote digital inclusivity for impaired users relying on accessibility features. We examined the capabilities and limitations of current accessibility verification tools to suggest strategies to incorporate validation tests into the development workflow. We identify accessibility verification challenges and offer automated validation methods where applicable to reduce manual labor. Our research was performed with an iterative design-based approach, resulting in a developer-approved framework that offers systematic design approaches and automated tests to simplify the compliance process. The framework provides developers and organizations with solutions to gradually improve accessibility compliance. To ensure industry relevance, we continuously obtained feedback from senior professional Android developers throughout the study to improve the implementation of accessibility features in the development process. According to prior research, Android accessibility features are rare in Android applications. With this study, we seek to change that and provide an equal application experience for all users.
Keywords: Android; application; mobile; development; accessibility; inclusion; automation; testing; verification; tooling